High prevalence of toxigenic Clostridium difficile in public space lawns in Western Australia - Moono, Peter (Sci Rep, 2017)
Clostridium difficile is a well-established hospital pathogen. Recently, it has been detected increasingly in patients without hospital contact. Given this rise in community associated infections with C. difficile, we hypothesized that the environment could play an important role in transmission of spores outside the hospital. Lawn samples (311) collected in public spaces in the metropolitan area of Perth, Western Australia, from February to June 2016 were cultured for C. difficile. C. difficile was isolated from the samples by direct and enrichment culture, and characterized by standard molecular methods using toxin gene PCR and ribotyping. The overall prevalence of C. difficile was 59%, new lawn (≤4 months old) was twice as likely as old lawn (>4 months old) to test positive (OR = 2.3; 95%CI 1.16–4.57, p = 0.015) and 35 C. difficile ribotypes were identified with toxigenic ribotype 014/020 (39%) predominating. The highest viable count from lawn soil samples was 1200 CFU/g. These results show that lawns in Perth, Western Australia, harbor toxigenic C. difficile, an important finding. The source of lawn contamination is likely related to modern practice of producing “roll-out” lawn. Further work should focus on identifying specific management practices that lead to C. difficile contamination of lawn to inform prevention and control measures.